A secure access method in English education network based on edge computing - Yu Bi; Tian Su (Alexandria Engineering Journal)
With the rapid progress of edge computing, authentication key negotiation protocols, as one of the key means to ensure secure communication, have attracted widespread attention. However, current authentication key negotiation protocols designed for mobile edge computing are often difficult to balance security and performance requirements. In order to solve this challenge, a secure access method is designed for an English education network environment oriented to edge computing. Firstly, this scheme adopts a lightweight physical unclonable function (PUF) as the trust guarantee for entities in the English education network and generates authentication credentials based on the identities of the terminal equipment and the server. Secondly, formal analysis by ROM and non-formal analysis verify that this scheme has strong security properties. Finally, communication consumption, computation consumption and memory usage are compared using to verify that this scheme demonstrates significant advantages in terms of efficiency.